Developing and designing a cost-effective beta website for the Armed Forces of the Philippines Main Library - Cruz, Kate Lora Q.; Surmieda, Janny S.; Apolinario, Rhea Rowena U. (Quezon City School of Library and Information Studies, University of the Philippines, Diliman, 2024)
The inception of this project stemmed from the lack of web presence of AFPML. Developing a website specifically for AFPML forms part of their efforts to market their library and connect with their immediate community. The website contains information about AFPML, its mother unit OSSSM. A website highlighting the collection housed in the physical library and select open-source electronic resources on military science and Filipiniana databases was also integrated into the site. Concerns on budget and technical background were raised and addressed by using an open-source website design tool with a simple and user-friendly design back end that allows basic website design and management. Feedback from the focus group and project consultant on the design, content and overall aspect were addressed as needed. There were communication issues resulting to the delay of the website acknowledgment from the sponsor, but the project manager still pursued to finish the project in good faith. It is recommended that AFPML consider using the website as a basis for their own domain-based website and explore available technology to aid in the service and impact efforts of the library. Additionally, collaborative activities and partnerships similar to this project can be explored to enhance the services and collection of the library.
Special Problem
Keywords: Armed Forces of the Philippines. -- Main Library; Library Web sites -- Design -- Case studies